Anode-Free Sodium Metal Batteries Based on Nanohybrid Core-Shell Templates - Lee, Min Eui; Lee, Seunggon; Choi, Jaewon; Jin, Hyoung-Joon; Han, Seungyong; Yun, Young Soo (WILEY-V C H VERLAG GMBH, 2019)
Anode-free sodium metal batteries (AF-SMBs) can deliver high energy and enormous power, but their cycle lives are still insufficient for them to be practical as a power source in modern electronic devices and/or grid systems. In this study, a nanohybrid template based on high aspect-ratio silver nanofibers and nitrogen-rich carbon thin layers as a core-shell structure is designed to improve the Coulombic efficiency (CE) and cycling performance of AF-SMBs. The catalytic nanohybrid templates dramatically reduce the voltage overshooting caused by metal nucleation to one-fifth that of a bare Al foil electrode (approximate to 6 mV vs approximate to 30 mV), and high average CE values of >99% are achieved over a wide range of current rates from 0.2 to 8 mA cm(-2). Moreover, exceptionally long cycle lives for more than 1600 cycles and an additional 1500 cycles are achieved with a highly stable CE of >99.9%. These results show that AF-SMBs are feasible with the nanohybrid electrode system.